Sistem Informasi Pengelolaan Inspeksi Berbasis Web Pada Dinas Pemadam Kebakaran Kota Surakarta - Ryan Arya Pramudya; Nibras Fa’id Muhammad; Sri Sumarlinda (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2025)
The manual management of fire protection inspection data at the Surakarta City Fire Department has caused delays and errors in recording, thus impacting the effectiveness of risk mitigation. This study aims to address these problems by designing and building a web-based inspection management information system. This research adopts the Rapid Application Development (RAD) method, with data gathered through observation, literature review, and interviews. The system was built using PHP, the Laravel framework, and a MySQL database. It enables officers to record inspection data digitally, manage archives automatically, and produce reports that are easily accessible to management. The implementation has proven effective in enhancing efficiency, speeding up the reporting process, and improving data accuracy and security to support better decision-making.